Die Entfernung der proximalen Handwurzelreihe = Proximal carpal row carpectomy - Spies, Christian; Unglaub, Frank (Operative Orthopädie und Traumatologie, 2016)
Objective: Resection of the proximal carpal row, termed proximal row carpectomy (PRC), is performed in order to treat pathologies of the proximal carpal row or radiocarpal joint between the scaphoid and scaphoid facet. It entails the articulation of the capitate and the lunate facet. Indications: Lunate necrosis, carpal collapse, joint infection with concomitant intercarpal ligament lesions. Contraindications: Severe cartilage lesions of the lunate facet and the capitate, wrist capsule laxity, rheumatoid arthritis, neuromuscular dysbalance of the wrist-covering soft tissue structures. Surgical technique: Dorsal approach to the wrist, incision of the third and fourth extensor compartments, resection and coagulation of the dorsal interosseous nerve, usage of a ligament-sparing capsule incision, identification of the proximal carpal row and inspection of cartilage of the lunate facet and capitate, mobilization and excision of the lunate, scaphoid and triquetrum, articulation of lunate facet and capitate is controlled clinically and fluoroscopically, wound closure, application of plaster slabs. Postoperative management: Immobilization of the wrist on plaster slabs for 2 weeks, removal of sutures after 14 days. Results: PRC is a surgical procedure with few complications. Satisfactory range of motion and grip strength could be preserved without limiting function of the upper extremity. Postoperative osteoarthritis of capitate and lunate facet did not correlate with the good clinical outcome.